2002
DOI: 10.1176/appi.ps.53.5.545
|View full text |Cite
|
Sign up to set email alerts
|

Rehab Rounds: Training Persons With Schizophrenia in Illness Self-Management: A Randomized Controlled Trial in Japan

Abstract: Despite the worldwide shift from inpatient to community-based treatment for individuals with severe mental illness, Japanese psychiatric services remain hospital based. In 1998, Japan had 29 psychiatric beds per 10,000 persons, twice as many as in most European countries and five times as many as in the United States (1). The reasons for Japan's slow transition to a community-based mental health system are both economic and cultural. For instance, 90 percent of psychiatric beds are in private for-profit hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 8 publications
1
30
0
6
Order By: Relevance
“…They cited six RCTs indicating that findings in support of the effectiveness of daily living skills training combined with social skills training were "strong" (15,(33)(34)(35)(36)(37). Of these, three RCTs examined the effects of the Social and Independent Living Skills Program and found the practice to be effective in improving independent living skills (33)(34)(35).…”
Section: Level Of Evidencementioning
confidence: 99%
See 3 more Smart Citations
“…They cited six RCTs indicating that findings in support of the effectiveness of daily living skills training combined with social skills training were "strong" (15,(33)(34)(35)(36)(37). Of these, three RCTs examined the effects of the Social and Independent Living Skills Program and found the practice to be effective in improving independent living skills (33)(34)(35).…”
Section: Level Of Evidencementioning
confidence: 99%
“…They cited six RCTs indicating that findings in support of the effectiveness of daily living skills training combined with social skills training were "strong" (15,(33)(34)(35)(36)(37). Of these, three RCTs examined the effects of the Social and Independent Living Skills Program and found the practice to be effective in improving independent living skills (33)(34)(35). The three remaining RCTs (15,36,37) of Functional Adaptation Skills Training with older adult patients and with Latino participants who had chronic psychosis were implemented by Patterson (a developer of the program) and colleagues (37).…”
Section: Level Of Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, several studies and mounting evidence has suggested that the CRM is an effective method for the rehabilitation of patients suffering from schizophrenia. [88][89][90][91][92] For example, the results obtained by Xiang et al revealed that CRM was an effective and feasible psychosocial intervention for Chinese patients with schizophrenia. 93 Specifically, the results indicated a significant improvement in social functioning, insight, and psychiatric symptoms in the CRM group as compared to the control group receiving only psychoeducation.…”
Section: Other Nonpharmacological Therapeutic Strategiesmentioning
confidence: 99%